Venous thrombosis in children and adolescents with Hodgkin lymphoma in Sweden. Issue 152 (April 2017) - Schönning, A; Karlén, J; Frisk, T; Heyman, M; Svahn, JE; Øra, I; Kawan, L; Holmqvist, B-M; Björklund, C; Harila-Saari, A; Ranta, S
Abstract: Introduction: Pediatric patients with Hodgkin lymphoma (HL) have several risk factors for venous thromboembolism (VTE). Although these patients are occasionally treated with thromboprophylaxis, no guidelines are implemented in Sweden. Scarce data from adult patients indicate an increased risk of VTE, but pediatric data is largely missing. Given the favorable overall survival of HL, there should reasonably be more focus on preventing complications. Materials and methods: We conducted a retrospective cohort study, including all patients registered in the Childhood Cancer Registry under the age of 18 years diagnosed with HL between January 2005 and December 2015 in Sweden. Results: Data was retrieved from the medical records of all 163 patients (100%) at six Swedish pediatric cancer centers. The incidence of VTE was 7.7% (symptomatic VTE 3.9%). The median follow-up was 3.4 years (range 0.3–10.5). Only five patients (3.1%) were treated with thromboprophylaxis. All VTE events occurred in the older age category (11–17 years) and all but one (92.7%) had a mediastinal mass. While the VTE did not significantly affect the treatment of HL, it caused increased morbidity and 2/12 developed a post-thrombotic syndrome. No significant risk factors for VTE were identified. Conclusions: VTE is a relatively common complication of HL and its treatment, causing increased acute and long-term morbidity. However, due to limited number of events we could not demonstrate risk-factors for VTE that would identify patients who might benefit from thromboprophylaxis. Highlights: The incidence of VTE is as high in pediatric Hodgkin lymphoma as in adults. VTE can lead to long-term morbidity in these children who have otherwise favorable prognosis. No time-point of increased VTE risk motivating routine short-term thromboprophylaxis was found.